Impact of Temperature Changes on the Growth, Development and Physiological Indicators of Wheat Varieties - F, Davronov; H. H., Khoshiev (American Journal of Biology and Natural Sciences, 2025)
This study investigates the physiological and biochemical responses of three wheat varieties (“Asr”, “Andijon-2”, and “Vassa”) grown in the semi-arid climate of the Sirdarya region (Uzbekistan) to short-term cold stress (7 °C for 8 hours). Experiments were conducted in the spring of 2024 with three replications under both control and stress conditions. Measurements included growth rate, photosynthetic activity, chlorophyll a content, and catalase enzyme activity. Results demonstrated that cold stress reduced growth rates by 25–35%, with “Andijon-2” showing higher photosynthetic efficiency (16.1 µmol CO₂/m²·s) and catalase activity (5.4 µmol H₂O₂/min/mg), indicating superior tolerance. Conversely, “Vassa” exhibited higher sensitivity, with a marked decline in chlorophyll a (20.9 mg/g) and catalase activity (4.8 µmol/min/mg). These findings provide critical insights for the selection of cold-tolerant wheat genotypes.